2014
DOI: 10.1039/c4lc00291a
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic-based platform for tumour spheroid culture, monitoring and drug screening

Abstract: The development of novel cellular models that can replace animals in preclinical trials of drug candidates is one of the major goals of cell engineering. Current in vitro screening methods hardly correspond with the in vivo situation, whereas there is a lack of assays for more accurate cell culture models. Therefore, development of automated assays for 3D cell culture models is urgently required. In this work, we present a SpheroChip system: a microfluidic-based platform for long-term 3D cell culture and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 38 publications
2
118
0
1
Order By: Relevance
“…The micro-moulding method has been explored to generate MSCs by fabricating complex structures using the lithography technique [109,110]. It has been documented that this micro moulding method can significantly reduce consumption of reagents, create desired concentration gradients of growth/signal factors and nutrients, allow high-density culture at a high cell-to-fluid volume ratio and decrease shear stress under the laminar condition in micro-scale structures [111].…”
Section: Micro-mouldingmentioning
confidence: 99%
“…The micro-moulding method has been explored to generate MSCs by fabricating complex structures using the lithography technique [109,110]. It has been documented that this micro moulding method can significantly reduce consumption of reagents, create desired concentration gradients of growth/signal factors and nutrients, allow high-density culture at a high cell-to-fluid volume ratio and decrease shear stress under the laminar condition in micro-scale structures [111].…”
Section: Micro-mouldingmentioning
confidence: 99%
“…Microwells [8,25,[87][88][89] and U-shaped microstructures [21,64,[90][91][92][93] have been designed for spheroid formation and culture in microfluidic platforms. These structures facilitate short-term [23,94], controllable and uniform diameter [22,95] and compact spheroid generation [32,92].…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Kwapiszewska et al developed the SpheroChip, consisting of disposable microfluidic chips for cell culture and a positioning plate, to culture human cell lines (i.e., HT-29 colon cancer cells and Hep-G2 hepatocytes). After the injection of anticancer drug 5-fluorouracil (5-FU), the dynamic changes on the metabolic activity of the cells in response to the drug could be monitored and analyzed continuously (Kwapiszewska et al, 2014). Ruppen et al observed a higher chemoresistance in primary co-culture 33 spheroids (i.e., primary lung cancer epithelial cells and primary pericytes) than in primary monoculture spheroids in a Lung-on-a-Chip model, which could serve as a more chemosensitive tumor model (Ruppen et al, 2015).…”
Section: D Cell Culture For Tumor-on-a-chipmentioning
confidence: 99%
“…Skin melanoma -Association between cancer and immune system (Businaro et al, 2013) Colon cancer Anticancer drugs (e.g., 5-fluorouracil) Anticancer efficacy; drug screening (Kwapiszewska et al, 2014) Breast cancer -Invasion (Trietsch et al, 2013) Photosensitizer (e.g., 5-aminolevulinic acid) and gold nanoparticles Photodynamic therapy evaluation (Yang et al, 2015) Lung cancer Anticancer drugs (e.g., gefitinib and masitinib) Anticancer efficacy; drug screening (Aref et al, 2013) Cisplatin Chemosensitivity evaluation (Ruppen et al, 2015) Brain glioma Anticancer drugs (e.g., vincristine and bleomycin)…”
mentioning
confidence: 99%